Effects of economic liberalization on gender earnings and the difference: The case of Hungary - Tseveenbolor Davaa; David M. Kiefer; Valeria Szekeres (The University of Utah, Department of Economics, 2018)
This paper examines the effects of macroeconomic policy reforms of trade and investment liberalization on gender earnings inequality during the post-transition period using panel data from Hungarian Wage and Earnings Survey and other statistical sources for 21 industrial categories. The results of the econometrics analysis with regression estimations show that while both women and men in foreign-invested enterprises earned more than their counterparts employed in domestically-owned enterprises, women earned less in export-oriented enterprises than in domestic market-oriented enterprises, while men's earnings are not significantly different in export versus domestic. Also foreign direct investment (FDI) inflows and export orientation contributed to a greater gender earnings difference. While FDI enterprises dominantly contribute to export growth in Hungary, the tests indicate that these two features had independent effects on earnings levels and gaps. These results hold after controlling for human capital variables (average age and education level in industry), industrial segmentation (female share of employment), labor productivity, and the economic cycle (unemployment rates). This study, a first for Hungary, contributes to research of wage gaps in post-transition economies.
Keywords: F6; J3; B54; 330; Gender earnings inequality; transition economy; economic liberalization; free trade; foreign direct investment